Mental health and interventions for parents of children with autism spectrum disorder: A narrative review and the relevance of this topic in Chile - Fernández Suárez, Macarena Paz (2019)
Autism Spectrum Disorder (ASD) affects neurodevelopment during the life of the person, also affecting the mental health of the parents. This article presents a narrative review of mental health research and interventions that promote mental health in parents of children from birth to nine years old. International and national databases between 2011 and 2015 were reviewed, of which 18 articles met the established criteria. The results show how the specific characteristics of ASD can affect the mental health of parents chronically, revealing also the scarcity of psychosocial interventions that promote the emotional well-being of these parents and, therefore, the need to assume a preventive role with this population.